Saussurea khunjerabensis (Asteraceae, Cardueae), a new species from Pamir - Li, Tian; Xu, Lian-Sheng; Chen, You-Sheng (Phytotaxa, 2022)
Saussurea khunjerabensis (Asteraceae, Cardueae), a new species from Taxkorgan county, Xinjiang, China, is described and illustrated. It belongs to Saussurea subgen. Eriocoryne because its capitula is aggregated in a densely congested hemispheric synflorescence and surrounded or half-surrounded by densely lanate uppermost leaves. This new species is similar to S. simpsoniana in its habit and linear uppermost stem leaves reflexed. However, it differs from S. simpsoniana by its stems usually unbranched and 11–25 cm high (versus usually branched and 2–12 cm high), lower leaf blade on both surfaces light green and densely white arachnoid lanate (versus adaxially dark green or purplish, sparsely arachnoid; abaxially grayish white, arachnoid tomentose to lanate), leaf margin usually pinnately lobed or divided (versus usually dentate to pinnately lobed, revolute), and lanate indumentum white or yellowish (versus lanate indumentum white or purple).